Developing tomorrow's leaders today : insights from corporate India - Wilson, Meena S. (Singapore : Jossey-Bass, 2010)
Today's large business organizations in India have a voracious need for effective managers and talented leaders; but demand far exceeds supply. This timely and practical book offers thoroughly-researched pointers on how Indian managers can become high-performing business leaders. The leadership development curriculum proposed in these pages is based on extracting lessons from on-the-job experience. Given that the workplace is the medium through which the essentials of leadership are learned, executives and managers at all levels need to know which experiences matter, what are the foremost le.
Developing Tomorrow's Leaders Today: Insights from Corporate India; Contents; Acknowledgments; About the Author; Foreword; Preface; 1 SEIZING THE MOMENT -- LEARNING FROM EXPERIENCES; 2 BOSSES WHO MAKE A DIFFERENCE; 3 CREATING CHANGE -- TAKING ON A TURNAROUND; 4 CREATING CHANGE -- LAUNCHING A NEW INITIATIVE; 5 THE HORIZONTAL MOVE -- JOB ROTATIONS AND TRANSITIONS; 6 CROSSING CULTURES; 7 TWO FUNDAMENTAL EXPERIENCES FOR NEW MANAGERS; 8 HARNESSING THE POWER OF EXPERIENCE; Appendix: THE LESSONS OF EXPERIENCE -- INDIA RESEARCH PROJECT; Index; About the Center for Creative Leadership
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Employees -- Training of -- India; Leadership -- India; Personnel -- Formation -- Inde; Leadership -- Inde; BUSINESS & ECONOMICS -- Mentoring & Coaching; BUSINESS & ECONOMICS -- Training; Employees -- Training of; Leadership; India